Incidencia de los sistemas informáticos en la gestión de la información académica de la Escuela de Conducción del Sindicato de Choferes Profesionales de Chimbo, año 2016. - Gómez Zavala, Edwin Javier (2017)
The present investigation was carried out by means of a field study applied in the Driving School, which revealed the inefficient management of the academic information existing in the institution, that is to say that the processes that are carried out generate difficulties such as: loss of information, Excessive use of time in carrying out activities, reports and reports delivered late, among others, which is why the hypothesis "The use of a computer system, will improve the management of academic information of the Driving School of the Professional Drivers Union Of Chimbo. " In order to fulfill the proposed objective, the use of methods, research techniques and data collection instruments was carried out, the information obtained determined the current situation in which the academic information is managed, at the same time this information was used as a basis for the Development of a computer tool which is responsible for managing the processes carried out by the institution. With the implementation and use of the Computer System (SI-GEST), the hypothesis presented in this research was demonstrated, the developed tool facilitated and expedited the registration and consultation of the information, reduced the response times in the various requirements requested by the users , That is to say, it was possible to improve the management of the academic information of the Driving School of the Professional Drivers Union of Chimbo, obtaining as main benefit excellent customer service and service.